2021
DOI: 10.1038/s41598-021-94155-y
|View full text |Cite
|
Sign up to set email alerts
|

Viability of acellular biologic graft for nipple-areolar complex reconstruction in a non-human primate model

Abstract: Many of the > 3.5 million breast cancer survivors in the US have undergone breast reconstruction following mastectomy. Patients report that nipple-areolar complex (NAC) reconstruction is psychologically important, yet current reconstruction techniques commonly result in inadequate shape, symmetry, and nipple projection. Our team has developed an allogeneic acellular graft for NAC reconstruction (dcl-NAC) designed to be easy to engraft, lasting, and aesthetically pleasing. Here, dcl-NAC safety and host-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 46 publications
(51 reference statements)
0
13
1
Order By: Relevance
“…Moreover, the resultant biological scaffold was cultured with MSCs and a high degree of bioactivity was obtained. More recently, from the same group, Caronna et al (2021) implanted those acellular grafts into two rhesus macaque non-human primates and successfully assessed the safety and host-mediated re-cellularization over 6 weeks, using the native nipples as control.…”
Section: Breast Tissue Scaffoldsmentioning
confidence: 99%
“…Moreover, the resultant biological scaffold was cultured with MSCs and a high degree of bioactivity was obtained. More recently, from the same group, Caronna et al (2021) implanted those acellular grafts into two rhesus macaque non-human primates and successfully assessed the safety and host-mediated re-cellularization over 6 weeks, using the native nipples as control.…”
Section: Breast Tissue Scaffoldsmentioning
confidence: 99%
“…In vivo studies confirm the biocompatibility of the NACgraft ™ , as well as its ability to regenerate a living NAC, including full epithelial coverage and integration of vasculature, at 6-weeks post-engraftment. 25,26 Specifically, these reports indicated that the newly re-cellularized graft harbored proliferating skin cells and confirmed the formation of a protective epidermal layer, as well as the presence of factors responsible for integrating the graft with surrounding host tissue. Notably, further analysis identified the presence of nerve regeneration in some of the grafts.…”
Section: Discussionmentioning
confidence: 77%
“…Existing NAC reconstruction techniques often cannot accurately capture the NAC's appropriate size, shape, and tactile properties. Current TE approaches to create lasting NAC projection utilize decellularized matrices, dermal grafts, and bioprinted scaffolds [32,19]. Decellularized NAC scaffolds implanted in non-human primates have shown similar epithelial coverage and vasculature to native tissue after 6 weeks post-engraftment.…”
Section: Biomaterials In Nipple Areolar Reconstructionmentioning
confidence: 99%
“…Decellularized NAC scaffolds implanted in non-human primates have shown similar epithelial coverage and vasculature to native tissue after 6 weeks post-engraftment. The projection, shape, color, and sensitivity characteristics of decellularized NAC scaffolds have not yet been reported [32]. Bioprinting allows for the generation of personalized implants fabricated from biocompatible materials and living cells, using an additive manufacturing approach.…”
Section: Biomaterials In Nipple Areolar Reconstructionmentioning
confidence: 99%